Development of conductive sheet composite based on kenaf fibre loaded with polyaniline for anti-static packaging application. - Austad, Azhan (2021)
This thesis reports the preparation of electrically conductive shielding sheets made up of kenaf fiber and polyaniline (KF/PANI) via in-situ polymerization method. This modification has the potential to be used as static shielding packaging, which will help to prevent the build-up of static electricity during the storage and transportation of electronic devices. The KF sheet was coated with PANI with varied concentrations from 1 to 10 wt%. It was tested for its tensile strength, tear test, burst test, water absorption test, DC conductivity, charge decay time, and shielding effectiveness. The modified sheets were suggested to be optimum at 5wt% of PANI coating based on mechanical, physical, and electrical evaluations. The mechanical integrity showed a slightly reduced compared to the neat KF sheet, and an optimum value of tensile strength, tear index, burst index, and folding endurance was 43.2±0.3 Nm/g, 20.9±1.4 mNm2/g, 5.7±0.8 kPa.m2/g and 296±10 times, respectively. The KF sheets' hydrophobicity increased as the PANI coating increased with optimum 6.15±0.4 % of moisture absorption at 53% relative humidity. It was found that KF/5PANI conductive sheet rapid charge dissipation at 0.87 seconds and a moderate shielding effectiveness value of -6.1 dB. The Fourier transform infrared spectroscopy (FTIR) revealed that the changes on wavenumber and new absorption peaks range from 1140 to 3500 cm-1 compared to the neat KF sheet. The scanning electron microscope (SEM) micrograph showed an excellent distribution of fibrous sheet morphology after PANI coating. Thermogravimetric analysis (TGA) suggested that PANI coating improves the modified sheet's thermal stability, where the thermal destruction took place when exposure achieved 300oC. The investigation led to the conclusion that the new conductive sheet has promising prospect as electrostatic charge dissipation (ESD) and electromagnetic interference (EMI) shielding material for protecting device potential applications.